Pregnancy rates in dairy cattle after three different, timed, breeding protocols - J. A. Cartmill; S. Z. El-Zarkouny; G. C. Lamb; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1999)
Synchronizing ovulation enables dairy producers to inseminate cows by appointment rather than after detected estrus. Three different, timed artificial insemination protocols using different combinations of prostaglandin F2α and gonadotropin-releasing hormone were used to synchronize ovulation in 702 lactating Holstein cows. Cyclicity, pregnancy rate, and embryonic survival rate from each treatment were compared. Our results indicate that all three treatments produced acceptable pregnancy rates in first lactation cows. However, for cows in their second or greater lactation, the treatment using prostaglandin F2α 12 days before the Ovsynch protocol improved pregnancy rates more than the other two.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Ovsynch protocol; Pregnancy rates; Timed a.i.